Leadership in a time of financial crisis: what do we want from our leaders?. Issue 5 (6th July 2015) - Haddon, Arlene; Loughlin, Catherine; McNally, Corinne
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to gain a nuanced understanding of what employees want from leaders in an organizational crisis context. Design/methodology/approach – The authors use a mixed methods approach to explore employee leadership preferences during organizational crisis and non-crisis times using the Multi Factor Leadership Questionnaire (Avolio and Bass, 2004), and qualitative interviews. The authors also investigate sex roles using the Bem Sex Role Inventory (Bem, 1981). Findings – The mixed method approach reveals some potential limitations in how leadership is typically measured. The qualitative findings highlight employees' expectations of leaders to take action quickly while simultaneously engaging in continuous communication with employees during crisis. None of the components of transformational leadership encapsulate this notion. Originality/value – The mixed methods approach is novel in the crisis leadership literature. Had the authors relied solely on the quantitative measures, the importance of continuous communication during crisis would not have been apparent. As a result of this approach, the findings suggest that widely used and accepted measures of leadership may not adequately capture leadership in a crisis context. This is timely as it aligns with current literature which questions the way this construct is operationalized (Van Knippenberg and Sitkin, 2013).